Ocean Floor Observation and Bathymetry System (OFOBS) seafloor images of the Weddell Sea, Antarctica collected during RV POLARSTERN cruise PS146 - Lilian Boehringer; Autun Purser; Lisa Chakrabarti; Chiara Papetti; Pedro Costa Rodrigues Furtado; Karsten Schimpf; Christopher Krämmer (PANGAEA, 2025)
During the RV POLARSTERN Expedition PS146 to the Weddell Sea from 2024-12-24 to 2025-03-10 the Ocean Floor Observation and Bathymetry System (OFOBS) was used to collect still images and video footage from various locations surveyed during the research cruise. The OFOBS consisted of a towed underwater camera system equipped with a high-resolution photo-camera (iSiTEC, CANON EOS 5D Mark III) set to automatically take images on a 1 min frequency ( extquotesingleTIMER extquotesingle) additionally to manually triggered images when particularly interesting objects appeared on the live feed ( extquotesingleMANUAL extquotesingle). The camera was mounted on a steel frame (140 L x 92 W x 135 H cm), together with two strobe lights (iSiTEC UW-Blitz 250, TTL driven), three laser pointers spaced with a distance of 50 cm used to estimate the size of seafloor structures. The OFOBS was additionally equipped with a front mounted pan and tilt 4K camera unit and 1 to 2 external battery powered GoPros. Further two triggerable 12l Nisken bottles were mounted on the sides of the device and a 3.5 m circumference fishing net was slung 2 m below the frame and still camera, therefore being in view of the still camera at all times of operation. The sidescan sonar system as well as the USBL positioning system were not in use during this expedition. In total, 10 OFOBS deployments were carried out. Image positions were based on the ships positions. Metadata in the form of iFDOs are available for each deployment containing a detailed description of the image data collection and curation process.